KINERJA KARYAWAN BERBASIS KOMPETENSI DENGAN MEDIASI KEPUASAN KERJA PADA INDUSTRI FASHION MUSLIM - Bisma Ekalayang Ichanudin; Rohimat Nurhasan; Wufron (Universitas Bina Taruna Gorontalo, 2025)
This study aimed to examine the effect of competence on employee performance, with job satisfaction as an intervening variable in the garut fashion muslim industry. The approaches used are quantitative with the type of causality research. The data analysis method used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. Data collection was carried out through literature studies and distributing questionnaires involving 78 employees with saturated sampling techniques. The research findings indicate that competence directly and significantly affects work satisfaction and employee performance. In addition, work satisfaction contributes positively and significantly to performance. Work satisfaction proved to be able to function as an intervening variable in the relationship between competence and performance. This means that the high competence possessed by employees will play a role in improving work performance and tend to be more confident in performing their duties, so there is a tendency for them to feel satisfied at work. Meanwhile, the fulfilment of work satisfaction, not only can directly affect the resulting performance, but also has an essential role in connecting the relationship between competence and performance.